2021
DOI: 10.1177/0972753120966495
|View full text |Cite
|
Sign up to set email alerts
|

Migrating Souvenir Bullet: The Management Dilemma

Abstract: The cranio-cerebral trauma following gunshot injuries has high mortality and morbidity, with 66% to 90% victims dying before reaching hospital and only half of those treated in hospital surviving. However, in case of most salvageable patients, the question which poses dilemma to treating physicians is the decision as to when and why remove the retained missile. A 21-year-old man was observing a gunfight in the street from his balcony. Suddenly something struck his forehead and there was a small amount of blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Moores concluded that migration did not usually change initial surgical management and that the fragment size and proximity to critical structures, including CSF outflow obstruction, should be used to determine the need for removal. 12 There are many instances in the literature where a strategy of nonremoval has acceptable outcomes, 7 , 16 , 17 but even though our patient did not have frank CSF obstruction, we felt that the position of the fragment within the lateral ventricle and its rapid migration mandated its removal. Aydoseli et al described a case in which intraventricular bullet migration caused hydrocephalus weeks after initial presentation.…”
Section: Discussionmentioning
confidence: 74%
“…Moores concluded that migration did not usually change initial surgical management and that the fragment size and proximity to critical structures, including CSF outflow obstruction, should be used to determine the need for removal. 12 There are many instances in the literature where a strategy of nonremoval has acceptable outcomes, 7 , 16 , 17 but even though our patient did not have frank CSF obstruction, we felt that the position of the fragment within the lateral ventricle and its rapid migration mandated its removal. Aydoseli et al described a case in which intraventricular bullet migration caused hydrocephalus weeks after initial presentation.…”
Section: Discussionmentioning
confidence: 74%
“…in contrast, other studies have suggested that retained bone and metal fragments are the risk factor for development of postoperative infection 22,24 and that the presence of intracranial retained foreign bodies promotes worse outcome in comparison with their absence 25 . Some studies found out that foreign bodies have the potential to initiate infection decades after the injury: brain abscess has been noted in patients 30 and 52 years after the injury around the retained shrapnel 6,23 . Long-term follow-up also revealed potential complications such as migration of the foreign bodies or development of the hydrocephalus 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found out that foreign bodies have the potential to initiate infection decades after the injury: brain abscess has been noted in patients 30 and 52 years after the injury around the retained shrapnel 6,23 . Long-term follow-up also revealed potential complications such as migration of the foreign bodies or development of the hydrocephalus 23 . Foreign bodies in the eloquent cortex may also increase the risk of posttraumatic epilepsy 16,24 .…”
Section: Discussionmentioning
confidence: 99%